Suture anchor stabilization of symptomatic accessory navicular in adolescents: Clinical and radiographic outcomes. (12th May 2020) - Kakihana, Masataka; Tochigi, Yuki; Yamazaki, Takayuki; Ohashi, Masanori; Ozeki, Satoru
Background: Screw fixation used in modified Kidner procedures to treat persistent symptomatic accessory navicular in adult cases is often challenging in adolescent cases with a small accessory fragment. The present study aimed to document the clinical effect of a suture anchor stabilization technique applicable to such cases where osteosynthesis is considered an ideal outcome. Methods: Consecutive clinical cases who received this surgical treatment from 2009 to 2016 were retrospectively reviewed. The focus of interest included radiographic union of the accessory bone, changes in symptoms evaluated using a validated clinical outcome scale introduced by the Japanese Society for Surgery of the Foot, and changes in the medial arch bony alignment measured in lateral weight-bearing plain radiographs. Results: Twenty-two feet in 15 individuals (11 females and 4 males, age at surgery 10–16 years) were identified. In 14 feet (64%), radiographic bone union was confirmed within 8 weeks postoperatively. At the final follow-up ranging 12–51 months postoperation, the clinical scores have significantly improved ( p < 0.001) to 96 ± 5.71 (mean ± standard deviation, range 87–100), from 54 preoperatively. Radiographic measurements revealed significant postoperative increase of the sagittal talar tilt angle ( p < 0.001, increment 4 ± 3°, range 0–11) and the talo-first metatarsal angle ( p < 0.001, increment 5 ± 4°, range 0–12). No significant changes were identified in the calcaneal pitch angle, first metatarsal tilt angle, calcaneo-navicular angle, and the navicular height. Conclusion: Despite the modest bone union rate, the clinical outcomes suggest distinct symptom-relieving effect, at least in the short- to midterm, while the radiographic measurements suggest positive biomechanical effects. The present suture-anchor stabilization concept appears to be a promising treatment option for persistent symptomatic accessory navicular in adolescent cases.